PERKEMBANGAN DATARAN PANTAI (COASTAL PLAIN) DAERAH KENDAL PROVINSI JAWA TENGAH - Ungkap M.Lumbanbatu (Pusat Survei Geologi, 2009)
A coastal plain area having dynamic charakterisitc. Understanding of Quaternary stratigraphy plays an important role in explaining the occurance of geological processes during the development of the coastal plain. Holocene stratigraphic sequence analysis reveals that the studied area has been influenced by several geological processes such as sea level rise and drop, and tectonic activities. These geological phenomenas are expected as the agents to change the directions of coastal plain development.Â Keywords: tectonics, quaternary stratigraphic sequences, sea level rise, sea level dropÂ